The Violent Pacifist: Ethics and Disorder in Sarah Waters' The Paying Guests. (14th February 2019) - Gildersleeve, Jessica; Sulway, Nike
Abstract: Sarah Waters' The Paying Guests (2014) deals with the aftermath of the First World War and with the tumultuous social changes and cultural trauma experienced in its wake. However, its gradual slippage from the drama of global warfare to the shabbiness of domestic crime marks a broader observation about the failure of both the war and the law to deliver justice. In this post-war environment there is no longer any certainty about morality, guilt, or responsibility. 'Being good' and 'doing good', Waters' novel shows, are no longer as synonymous as they might once have appeared.